(untitled) (Fiep Bulletin - online, 2014)
The objective of this research was to verify how healthy habits contents are being showed during the Physical Activity classes at a public school. The sample corresponds to 103 students and 4 physical education professors from high school. The research methods were: reading of the Pedagogic Political Project of the school; afterwards the Perception of Healthy Habits Questionnaire (PHAQ) was applied with two more open questions. The results obtained by the research showed the following relationship: healthy habits in physical education classes shows only the physical activity aspects. The teachers informed in the open question that they do not follow the work of their students. They also reported to have difficulties related to some items from the PHAQ. This information is important and necessary to show the importance of training courses for teachers, because in these courses they can review contents of healthy habits for students and understand their influence inside their schools.